Let the three numbers be x, y, and z. Then we can say:

(1) x + y + z = 120

(2) y = 3z

(3) x = z + 10

Using the second equation (2) we can replace "y" (in the first equation) by "3z". And using the third equation (3), we can replace "x" (in the first equation) with "z + 10". The new first equation is then:

(1 modified) (z + 10) + (3z) + z = 120

Combining like terms we get:

5z + 10 = 120

5z = 110

z = 110/5 = 22

Since x = z + 10 then x = 22 + 10 = 32

Since y = 3z then y = 3(22) = 66

First Number is 32

Second Number is 66

Third Number is 22